Analysis of the Influence of Accounting Training and Education Levels on the Use of Accounting Information in Micro, Small and Medium Enterprises - Ruliana, Titin; Solihin, Danna; Kulsum, Umi; Heriyanto, Heriyanto (Journal of Nonformal Education, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy, contributing significantly to gross domestic product (GDP) and labor absorption. However, many MSMEs face challenges in financial management, especially in the effective use of accounting information. Accounting training and the level of education of business owners are key factors that can affect the ability of MSMEs to manage accounting information. This study aims to analyze the influence of accounting training and education level on the use of accounting information in MSMEs in Samarinda City. The research method used is a quantitative approach with a survey design, which allows the collection of data from a large number of respondents. The research participants consisted of 100 MSME actors operating in Samarinda City, who were selected using the Random Sampling technique. Data was collected through questionnaires designed to measure variables of accounting training, level of education, and use of accounting information, with closed-ended questions using the Likert scale. Data analysis was carried out using multiple linear regression techniques to test the simultaneous influence of accounting training and education levels on the use of accounting information. The results of the study show that accounting training has a significant positive effect on the use of accounting information, and the level of education also has a significant positive effect. These findings provide important insights into the importance of training and education in improving the quality of accounting information management in the MSME sector.